Resection of Left Atrial Myxoma in a Patient with Retrosternal Gastric Tube: a Case Report - Pomerantzeff,Pablo Maria Alberto (2017)
Abstract The median sternotomy remains the standard approach in cardiovascular surgery but, in some conditions, it can be considered difficult to perform, especially in patients with history of esophagectomy. This case report describes a successful resection of a left atrial myxoma through a right anterolateral thoracotomy approach in a patient with a previous retrosternal gastric tube reconstruction. The decision for the best surgical approach was made after a heart surgery team discussion. Through this surgical access, a safe and excellent exposure of the left atrium was possible, and a complete resection of the myxoma was performed without any injury to the gastric tube.